PENGARUH KEGIATAN PAPER QUILLING TERHADAP PERKEMBANGAN MOTORIK HALUS ANAK - Ibrahim, Nur Icca; Elvira, Melly (Jurnal Penelitian Anak Usia Dini, 2024)
This study aims to determine the development of children's fine motor skills. The implementation of the study was motivated by the problem of fine motor development of group A children at Insan Madani Plus Kindergarten, Malang City, which is still not optimal. This study used a Quassy experimental research design with One-Group Pretest-Posttest Design. The research was conducted at Insan Madani Plus Kindergarten Malang City in March 2023. The sample in this study were all children in group A of TK Plus Insan Madani Malang City, totaling 7 children. Data collection techniques using observation, for data analysis using the Wilcoxon Test.Based on the results of the study, using Pre-Test (before treatment) and Post-Test (after treatment) and data analysis conducted using the Wilcoxon test obtained a Z value of -2.379 and Asymp. Sig. (2-tailed) of 0.017, it can be concluded that there is a significant difference between posttest and pretest. The assumption in the Wilcoxon test is that if the Asymp.Sig value is <0.05, then the alternative hypothesis (Ha) is accepted, whereas if the Asymp.Sig value is >0.05, then Ha is rejected. In this case, since the Asymp.Sig value (0.017) < 0.05, Ha is accepted which indicates that there is a significant difference between the posttest and pretest. Therefore, it can be concluded that paper quilling activities have a significant effect on the fine motor development of children aged 4-5 years in group A of TK Plus Insan Madani Malang City.